2015
DOI: 10.3109/02713683.2015.1004719
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole- and Resveratrol-Induced Delay of Retinal Ganglion Cell Death in an Experimental Model of Glaucoma

Abstract: When used either alone or in combination, both riluzole and resveratrol, two agents with different mechanisms of action in glaucoma, significantly delayed RGC loss in this study's experimental glaucoma model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 57 publications
2
47
0
1
Order By: Relevance
“…28,29 It has been reported that pretreatment or posttreatment with RES, primarily by oral administration, provides neuroprotection in glaucoma, but the underlying mechanisms were largely unknown. [30][31][32] Considering that many studies have shown that oral bioavailability of RES was less than 1%, which has possibly caused discrepancies between many in vitro and in vivo studies on RES, pretreatment plus posttreatment with RES has been performed in our retinal I/R injury models. 38,39 We further investigated the mechanisms underlying RES's protective effects on glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 It has been reported that pretreatment or posttreatment with RES, primarily by oral administration, provides neuroprotection in glaucoma, but the underlying mechanisms were largely unknown. [30][31][32] Considering that many studies have shown that oral bioavailability of RES was less than 1%, which has possibly caused discrepancies between many in vitro and in vivo studies on RES, pretreatment plus posttreatment with RES has been performed in our retinal I/R injury models. 38,39 We further investigated the mechanisms underlying RES's protective effects on glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Several recent reports have shown that pretreatment or posttreatment with RES effectively protects injured RGCs in experimental glaucoma models. [30][31][32] However, the precise mechanisms by which RES protects RGCs are still largely unknown.…”
mentioning
confidence: 99%
“…It is believed that neuroprotective drug from RGCs against apoptosis could be an effective way in the management of glaucoma. Pirhan et al (2016) studied the effects of RSV and riluzole on the survival of RGCs in rats. They concluded that combined therapy results in high RGCs protection.…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%
“…The detailed molecular mechanisms underlying riluzole and RSV neuroprotective effects are not clear. Another study using young–adult Thy1‐yellow fluorescent protein (YFP) and C57BL mice confirmed previous study observations which referred based on dendrite RGCs protection role of RSV (Pirhan et al., 2016). Razali and colleagues performed reduction in IOP using the topical use of trans‐resveratrol induced in SIOH rat models.…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%
“…Experimental induction of elevated IOP is frequently used to generate animal models of POAG [41]. It was reported that resveratrol significantly delayed RGC loss in a glaucoma model induced by injecting hyaluronic acid into the rat anterior chamber [42]. Given that RGC damage is a characteristic of both LHON and POAG, we conducted a literature search for animal models of RGC degeneration in which the compounds discussed above were tested.…”
Section: Protective Effects Of Retinal Ganglion Cellsmentioning
confidence: 99%